EFLA 945 restricts AIM2 inflammasome activation by preventing DNA entry for psoriasis treatment. (March 2020) - Chung, I-Che; Yuan, Sheng-Ning; OuYang, Chun-Nan; Hu, Sheng-I; Lin, Hsin-Chung; Huang, Kuo-Yang; Lin, Wei-Ning; Chuang, Yu-Ting; Chen, Yu-Jen; Ojcius, David M.; Chang, Yu-Sun; Chen, Lih-Chyang
Highlights: EFLA 945, a product of red grape vine leaf extracts attenuate the AIM2 inflammasome. EFLA 945 interferes with the entry of extracellular DNA into the cells. EFLA 945 attenuates imiquimod-induced psoriasis in mouse model. EFLA 945 attenuates imiquimod-induced inflammatory responses in psoriatic skin. Abstract: Psoriasis is a chronic inflammatory skin disease that affects about 2% of the general population. Activation of the Absent in Melanoma 2 (AIM2) inflammasome is crucial for immune defense, but it can also cause inflammatory and autoimmune diseases, including psoriasis. We currently lack an AIM2 inflammasome inhibitor that could be used therapeutically. Here, we show that EFLA 945, a safe product of red grape vine leaf extracts, can restrict AIM2 inflammasome activation. Mechanistically, EFLA945 prevents DNA entry into THP-1-derived macrophages, and thereby inhibits cytoplasmic DNA-dependent apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization, caspase-1 activation, and the secretion of interleukin (IL)-1β and IL-18. The major phytochemicals of EFLA 945, resveratrol and peonidin 3-O-glucoside (P3G), appear to be the potential bioactive compounds responsible for its ability to restrict AIM2-dependent IL-1β secretion. Importantly, in an in vivo mouse model, EFLA 945 attenuates imiquimod (IMQ)-induced psoriasis-related pro-inflammatory responses in topical psoriatic skin, including caspase-1 activation, IL-1β maturation, and IL-17 production, and decreases the severity of psoriasis. Together, these results demonstrate that the safe natural product, EFLA 945, can restrict the AIM2 inflammasome activation through preventing DNA entry and may prove beneficial for treating psoriasis.